EXAMINING THE ABILITY OF SHARIA ECONOMICS TO BE IN HARMONY WITH CONVENTIONAL ECONOMICS - Kandiarum, Dyyah; Putri, Leilani; Rahmadhani , Ersa; Abdurrahman , Thoriq; Waluyo (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2024)
This research looks at how sharia and conventional economics can be harmonized. Sharia economics is increasingly popular as an alternative, but there are some obstacles. This includes regulations, the state of politics, economics, and public understanding. This study uses a qualitative approach to examine elements such as government policies, business practices, and community responses that influence the harmonization of these two systems. It is stated that collaboration between educational institutions, businesses, and regulators is essential to integrate the two systems well. The results of the study show that the understanding and practice of sharia economics are different from conventional economics; However, it is possible that the two can be adjusted to a shared commitment. To maximize Indonesia's economic potential, it is necessary to improve education, improve regulations, and cooperation between Islamic and conventional financial institutions. It is hoped that the integration of these two systems will encourage inclusive and sustainable economic development.